Significant Shortening of Leukocyte Telomere Length in Korean Patients with Bipolar Disorder 1 - Joo, Eun-Jeong (Clin Psychopharmacol Neurosci, 2021)
OBJECTIVE: Telomere shortening has been seen in major psychiatric disorders, including major depressive disorder. However, only a few small studies have examined this in bipolar disorder (BD). We compared the telomere length in patients with BD1 or BD2 with that in matched healthy controls. METHODS: We included 215 patients with BD (128 BD1, 87 BD2) and 204 age- and sex-matched healthy controls. Relative telomere length was determined by quantitative polymerase chain reaction. The patients and controls were compared separately for age groups, sex, and BD subgroups (BD1 and BD2). RESULTS: We found significant telomere shortening in patients with BD1 (p < 0.001), but not in patients with BD2. In male patients with BD1, the 30−39 year age group had significant shortening of telomere length than controls (p = 0.01). Female patients with BD1 in the 19−29-year age group had significantly shortened telomeres compared to the controls (p < 0.01). CONCLUSION: Our results suggest a significant reduction in telomere length in BD1. Telomere shortening would be a potential biomarker for BD.